Performance efficiency and energy harvesting of single and multi-duck WEC under diverse geometrical and operational scenarios - Mostafa Jafarzadeh Khatibani; Hassan Ghassemi; Mahmoud Ghiasi; Guanghua He (Energy Conversion and Management: X)
This study examines the hydrodynamic behavior, performance efficiency, and power absorption of single and multi-duck pitching-type wave energy converters (WECs). The comparison and validation of computational results have been conducted with previously published experimental data. The aim is to identify the most suitable WEC size for the most probable wave condition of the Astara port in the Caspian Sea while obtaining the optimum power take-off (PTO) damping coefficient for different geometry ratios (GRs). The power extraction and performance efficiency are then calculated at various wave heights and periods, considering both two-way and one-way PTO systems. It is found that the performance efficiency of the duck WEC with a GR of 3.2 devotes higher efficiency, and also, by engaging the two-way PTO system, absorbs 45.4% more power. The interaction factor accounts for the interference between the WECs due to their proximity. The study thoroughly examines the dynamic response, performance efficiency, power extraction, and interaction factor of the WEC under varying ranges of regular wave characteristics. Overall, this study provides valuable insights into the behavior and efficiency of single and multi-duck WECs in regular waves and can aid in developing and optimizing wave energy technologies.